LIVING WITH THE LEGACY OF THE REFORMATION: CONFESSIONAL IDENTITIES AND ECUMENISM IN TESTIMONIES OF GERMAN-SPEAKING WOMEN - Regina Heyder; Ute Leimgruber (Asian Horizons, 2017)
In Germany, after World War II flight and expulsion of about 12 million Germans from the eastern territories brought an end to a relatively stable, small-scale denominational landscape, where contrasts between denominations moulded the religious identity of Christians. The eyewitness reports of German-speaking Catholic and Protestant women tell stories about denominational identities serving as a means for discrimination and exclusion but also stories about learning processes that may serve as a model for transgressing boundaries in today’s increasingly multi-religious society. According to the narratives, the commitment for ecumenism is usually stimulated by biographical momentums like encounters or a personal crisis originating from denominational division. Ecumenical experiences will lead to theological reflection—with respecting the differences between denominations as an integral part of ecumenism on the one hand, and a transformation of the participants on the other hand. For the future, however, the vision and longing of the authors is a common Christian testimony in today’s world.